Preparation and evaluation of dl-praeruptorin A microemulsion based hydrogel for dermal delivery. (18th August 2015) - Zhang, Xianhua; Wu, Yueping; Hong, Ying; Zhu, Xuan; Lin, Liang; Lin, Qingjiang
Abstract: The purpose of the present investigation was to develop and optimize the microemulsion (ME) as a transdermal system for Pd-Ia, a poor water soluble and low bioavailable drug. The pseudo-ternary phase diagrams were constructed for various ME formulations including oleic acid as the oil phase, Cremophor RH40 as the surfactant, ethanol as the cosurfactant, and water. The maximum cumulative amount permeated through rat abdominal skins per unit area in 32 h ( Q 32 ), and the maximum flux were evaluated using the Franz diffusion cell in order to optimize the ME formulation. The results indicated that the optimized ME formulation was composed of oleic acid (5%, W/W), Cremophor RH40 (13.33%, W/W), ethanol (26.67%, W/W), and water (55%, W/W); the maximum cumulative amount of Pd-Ia was 354.330 ± 12.006 μg cm −2, the maximum flux was 11.467 ± 0.500 μg cm −2  h −1 . ME-gel was administered transdermally to rats. The mean plasma concentration of Pd-Ia following transdermal application of ME-gel could be maintained for 32 h at least and the half-life was evidently prolonged. It shows that the ME-gel could be a promising vehicle for dermal delivery of Pd-Ia.